UPAYA PEMERINTAH PROVINSI PAPUA DALAM MENYELESAIKAN KLAIM BATAS WILAYAH KOTA JAYAPURA DENGAN KABUPATEN JAYAPURA - Gilberd R. Youkwart (JURNAL KEBIJAKAN PUBLIK, 2020)
This article aims to explain and analyze the efforts of the Papua Province government in facilitating the settlement of the boundaries of the Jayapura City Government with the Jayapura Regency Government, then to find out and analyze the factors that support and hinder the efforts of the Papua Province government in facilitating the settlement of the boundaries between the Jayapura City Government and the Regency Government. Jayapura and third, to find out and analyze the social impacts that occur in the scope of border communities and the solutions provided by the Papua Provincial Government in facilitating the settlement of the boundaries of the Jayapura City Government with the Jayapura Regency Government. This study uses a qualitative research method approach (qualitative research) that seeks to construct reality and understand its meaning, so it is very concerned about the process, events and authenticity. The data analysis technique used in this study is interactive analysis. This model has four components of analysis, namely: data collection, data reduction, data presentation, and drawing conclusions. The results showed that the Strategy for claim settlement turned out to have been carried out several times mediated, facilitated by the Government of the Governor of Papua, of all the mediations carried out did not also get a bright spot regarding the problem of resolving border claims. Because, the two disputed local governments still survive based on the legal basis that they guide each of them. Factors supporting the implementation of the policy to handle regional boundary claims between Jayapura City and Jayapura Regency related to the laws and regulations regarding the handling of regional boundary claims have been implemented to the maximum extent at all levels. While the inhibiting factor is the uncertainty of one of the parties to the dispute regarding the exercise of authority carried out by the Papua Province government. In the exercise of its authority, the Papua Province government is less socialized to the bureaucratic ranks of both parties to the dispute, the limited budget and the shortage of personnel in the settlement of the poultices. the limit in the field. Social Impacts That Occur on Border Society Scope and Solutions Provided by the Government of the Papua Province in Facilitating the Settlement of Jayapura City Government Boundaries With the Jayapura Regency Government include infrastructure development, health development, education development and economic development.